Diversidad y desigualdad : las razones del socialismo / Manuel Monereo Pérez, Pedro Chaves (coordinadores) ; Pablo González Casanova ... [et al.] - Monereo, ManuelChaves, PedroGonzález Casanova, Pablo (1922-)
Bibliografía